Nomenclatural Changes in Indian Plants - Raizada, M. B. (Indian Forester, 1966)
The nomenclature of a large number of Indian plants is adjusted in conformity with the Rules of Nomenclature. Some of the changes refer to changes in attribution, which have been necessitated by the strict application of Art. 33 of the Code, Edition 1961. Fifteen new combinations are proposoed in this paper.